BACON VE VICO'DA İLÂHÎ VE ÎNSANÎ BİLGİ - Sema Önal Akkaş (Felsefe Dünyası)
In this article, Bacon's and Vico's ideas on divine and human knowledge are compared. According to Bacon, the sphere of knowledge is the sphere of nature. For Vico, the sphere of knowledge is human deeds. For both philosophers, the sphere of being is different. Bacon asserted that knowledge of nature could be gained, but for Vico it cannot. Granted that God created Nature and He knows it perfectly. But human beings can only know their deeds inasmuch as they create them. Vico, who applied to inductive reasoning in the case of human reality, was influenced by Bacon in this regard.